Recent developments in the synthesis and stability of metal ferrite nanoparticles. (March 2019) - Imran Din, Muhammad; Rafique, Faria; Hussain, Muhammad Sadaf; Arslan Mehmood, Hafiz; Waseem, Sadia
This article presents a comprehensive review on the synthesis and stability of ferrite nanoparticles such as nickel ferrite (NiFe2 O4 ), zinc ferrite (ZnFe2 O4 ), manganese ferrite (MnFe2 O4 ), iron ferrite (Fe2 O3 ), cobalt ferrite (CoFe2 O4 ) and also mixed nanoparticles. Different synthetic methods for ferrite nanoparticles have been reviewed such as co-precipitation, thermal decomposition and hydrothermal, microwave-assisted and sonochemical methods. The effect on the stability of different capping agents like canola oil, glycerol, sodium dodecyl, sodium citrate, oleic acid, Triton-100 and sodium dodecyl benzene sulfonates has also been studied.